What do users care about? Research on user behavior of mobile interactive video advertising. Issue 10 (October 2022) - Gu, Chao; Lin, Shuyuan; Sun, Jie; Yang, Chun; Chen, Jiangjie; Jiang, Qianling; Miao, Wei; Wei, Wei
Abstract: Mobile interactive video advertising is a relatively new type of media. A combination of interactivity and narrative is used to tell the video story to the audience. This study studied in three steps on mobile interactive video advertising to determine the design basis that should be paid attention to. Firstly, the research framework is proposed through expert interview and qualitative coding of the interview text. Secondly, research samples are made through surveys and conference discussions. The samples were designed into 30 types containing various interactive narrative and involvement. Finally, the qualitative results are verified in a quantitative way. The results show that in order to improve the audience's purchase intention, more attention should be paid to interactive narrative, subjective video quality assessment, immersion, satisfaction, and product involvement. Abstract : Electronic commerce, Interaction design, Media arts, Psychology.